COMPARATIVE ANALYSIS OF REGIONAL TOURISM IN TASHKENT AND SAMARKAND: RESOURCES, DEVELOPMENT, AND COOPERATION - Xotamkulova , Odina; Goyibnazarova , Shahnoza (Scientific practical conference, 2025)
This article provides a comparative analysis of regional tourism in Uzbekistan, focusing on Tashkent and Samarkand. It examines natural and man-made tourism resources, visitor flow and seasonality, the level of tourism development, and opportunities for regional cooperation. The article also highlights future development trends, including sustainable tourism practices and the creation of integrated tourism routes